Taḥlīlu al Isti’ārati al Taṣrīḥiyyati wa al Isti’ārati al Makniyyati fī Syi’ri Nizār Qabbānī (Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Bayāni) - Fitriani, Ayu; Yusuf, Muhammad (Al-Uslub: Journal of Arabic Linguistic and Literature, 2022)
Analysis of the Tasrihiyyah Wal Makniyyah Istiarah in the Poetry of Nizar Qobbani. Jambi: Arabic Literature Study Program, Faculty of Adab and Humanities, State Islamic University of Sulthan Thaha Saifudin Jambi. Nizar Qobbani is a male poet in modern times who is famous for his poems about women and love. The discussion in this thesis is a study of syi'ir Nizar qobbani with the Balaghah Science approach related to Bayan Science, Ma'ani Science, Badi Science'. As for the discussion of Istia'roh, it has the meaning of tasybih that one of its dhorof is removed, and the relationship between the meaning of haqiqi and its majazi is musyabahah. Isti'aroh is also a borrowing of lafadz, but what is desired is not the original meaning, and there is a qarinah that what is desired is not the original meaning. In this thesis, the researcher will discuss Isti'aroh in Nizar Qobbani's syi'ir, because Nizar Qobbani's syi'ir contains many balagha elements, but the dominant one is isti'aroh. Therefore, the researcher discusses Isti'aroh Tasrihiyyah and Makniyyah in syi'ir Nizar Qobbani. The purpose of this study is to describe and determine the meaning of (1) istiarah (2) poetic sentences containing rest in Nizar Qobbani's poetry, (3) and (4) the purpose of revealing the meaning contained in Nizar Qobbani's syi'ir. The method used in this research is descriptive qualitative. In this discussion, there are 17 Istia'rah Tasrihiyah and 4 Istia'rah Makniyah and the meanings contained in the poems containing the Tasrihiyah and Makniyah Istia'rah. This study aims to make it easier for readers to understand the implied meaning in Nizar Qobbani's poetry.